Factors In Influencing User Acceptance Of Mobile Commerce In Malaysia - E, Ching Loo (2007)
Mobile Internet and Mobile Commerce show great potential in Malaysia with their fast growing rate of mobile users. However there are also many barriers against their adoption progress, thus it is essential to investigate the influencing factors of user's acceptance towards mobile commerce.